Odpowiedź :
Odpowiedź:
[tex]a)\\\\3\frac{1}{2}-x=1\frac{1}{4}\\\\-x=1\frac{1}{4}-3\frac{1}{2}\\\\-x=\frac{5}{4}-\frac{7}{2}\\\\-x=\frac{5}{4}-\frac{14}{4}\\\\-x=-\frac{9}{4}\\\\-x=-2\frac{1}{4}\ \ /\cdot(-1)\\\\x=2\frac{1}{4}\\\\\\b)\\\\7\frac{3}{4}-y=3\frac{1}{2}\\\\-y=3\frac{1}{2}-7\frac{3}{4}\\\\-y=\frac{7}{2}-\frac{31}{4}\\\\-y=\frac{14}{4}-\frac{31}{4}\\\\-y=-\frac{17}{4}\\\\-y=-4\frac{1}{4}\ \ /\cdot(-1)\\\\y=4\frac{1}{4}[/tex]
[tex]c)\\\\1\frac{1}{4}+z=4\frac{1}{2}\\\\z=4\frac{1}{2}-1\frac{1}{4}\\\\z=4\frac{2}{4}-1\frac{1}{4}\\\\z=3\frac{1}{4}[/tex]
Odpowiedź:
A) 3 i 1/2 -x= 1 i 1/4
x= 3 i 12- 1 i 1/4
- x= 3 i 2/4 - 1 i 1/4
x= 2 i 1/4
spr.. 3 i 1/2 - 2 i 1/4= 1 i 1/4
3 i 2/4 - 2 i 1/4= 1 i 1/4
1 i 1/4= 1 i 1/4
L=P
B) 7 i 3/4 - y= 3 i 1/2
y= 7 i 3/4 - 3 i 1/2
y= 7 i 3/4 - 3 i 2/4
y= 4 i 1/4
spr.. 7 i 3/4 - 4 i 1/4= 3 i 1/2
3 i 2/4= 3 i 1/2
3 i 1/2= 3 i 1/2
L=P
C) 1 i 1/4 + z = 4 i 1/2
z= 4 i 1/2- 1 i 1/4
z= 4 i 2/4- 1 i 1/4
z= 3 i 1/4
spr.. 1 i 1/4 + 3 i 1/4= 4 i 1/2
4 i 2/4= 4 i 1/2
4 i 1/2= 4 i 1/2
L=P
Szczegółowe wyjaśnienie: